2016
DOI: 10.1111/dme.13094
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of insulin pump therapy: reduction of hypoglycaemia and impact on glycaemic control

Abstract: CSII therapy achieves and maintains its efficacy mainly in terms of reducing severe hypoglycaemia. In the whole group of patients, the reduction in HbA1c is transient and disappears after 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Those with initial hypoglycaemia unawareness (Gold score ≥ 4) enjoyed an improvement in score on CSII (4.9 vs. 3.8, P = 0.01), with~38% regaining awareness. Quirόs et al [38] reported a 74% reduction in severe hypoglycaemia, sustained over the 5 years of the study, in a subgroup of people at a Spanish clinic who transferred to CSII because of recurrent severe hypoglycaemia on MDI.…”
Section: Hypoglycaemiamentioning
confidence: 91%
See 1 more Smart Citation
“…Those with initial hypoglycaemia unawareness (Gold score ≥ 4) enjoyed an improvement in score on CSII (4.9 vs. 3.8, P = 0.01), with~38% regaining awareness. Quirόs et al [38] reported a 74% reduction in severe hypoglycaemia, sustained over the 5 years of the study, in a subgroup of people at a Spanish clinic who transferred to CSII because of recurrent severe hypoglycaemia on MDI.…”
Section: Hypoglycaemiamentioning
confidence: 91%
“…Quirόs et al . reported a 74% reduction in severe hypoglycaemia, sustained over the 5 years of the study, in a subgroup of people at a Spanish clinic who transferred to CSII because of recurrent severe hypoglycaemia on MDI.…”
Section: A Summary Of the Evidence For Csii Effectivenessmentioning
confidence: 99%
“…Quiros et al, 64 from Barcelona, followed 151 patients on pump therapy for 5 years. Overall, HbA 1c was reduced from a mean of 8.0% at baseline to 7.8% at 5 years.…”
Section: Overview Of Evidence Base For Pump Therapymentioning
confidence: 99%
“…There was a marked reduction in severe hypoglycaemia. 64 Rosenlund et al 65 from Denmark looked at the effects of 4 years of pump therapy on albuminuria compared with an unmatched group on MDI. On pump therapy, HbA 1c fell from 8.4% to 7.8%, maintained to 4 years.…”
Section: Overview Of Evidence Base For Pump Therapymentioning
confidence: 99%
“…Despite CSII being superior to MDI [7] in terms of efficiency and safety it does not provide long-lasting results in lowering the glycated hemoglobin (HbA 1c ) level [8]. While being a golden standard for treatment of type 1 diabetes, CSII cannot be of use for patients with type 2 diabetes because they seem not to benefit from this type of treatment [9].…”
Section: Insulin Pumpsmentioning
confidence: 99%